Development anomaly and non-vitality: Two case reports - Sivakumar Kailasam; Boopathi Thangavel; Sebeena Mathew; Arjun Kesavan Purushotaman Das; Harikaran Jayakodi; Karthick Kumaravadivel (Wolters Kluwer Medknow Publications, 2012)
Anatomic aberrations are seen in human dentition. The maxillary incisor region of the permanent dentition where these anatomical aberrations are commonly seen is considered an area of embryonic hazard. Aberrations affecting the internal and external morphology can at times be the cause of complex pathological conditions involving the pulpal and periodontal tissues and can pose a challenge to the clinician for the diagnosis and clinical management. Detecting and treating the anomalies at an early phase is essential as it poses a threat for the loss of vitality of the concerned teeth. The aim of this paper is to highlight the fact two different developmental anomalies of maxillary incisors, namely palatoradicular groove and Turner's hypoplasia, led to the loss of vitality of the same.